Recurrent diabetic myonecrosis in an African American woman with long-standing uncontrolled type 2 diabetes: a case report - Varsha Kurup; Ying Nagoshi; Marie Rivera-Zengotita; Edlira Maska (Journal of Medical Case Reports, 2023)
Abstract Background Diabetic myonecrosis, also called diabetic muscle infarction, is an uncommon complication of uncontrolled diabetes mellitus and is frequently underdiagnosed. The objective of this case report is to highlight the challenges in the early diagnosis and treatment of this disease. Case presentation A 51-year-old African American woman with a long history of uncontrolled diabetes mellitus presented to her primary care physician with right thigh pain. A diagnosis of diabetes myonecrosis was made on the basis of magnetic resonance imaging, biopsy, and negative autoimmune panel. After failing conservative treatment, the patient was treated with prednisone with gradual improvement of her symptoms. However, she had a recurrence of myonecrosis almost one year after her original presentation, which was also treated with prednisone. The recurrence had a shorter course and the patient recovered well. Challenges to the treatment in this patient were her debilitating pain and her underlying chronic kidney disease. Conclusions A high index of suspicion for diabetic myonecrosis is necessary when a patient with diabetes presents with unilateral focal leg pain and swelling. Magnetic resonance imaging and biopsy can help confirm the diagnosis. Prednisone may be considered in patients who lack spontaneous regression with just rest. Educating healthcare professionals about this uncommon condition is of utmost importance in avoiding unnecessary testing and inappropriate treatment.